Thrombocytopenia in Neonates Undergoing Exchange Transfusion of Blood for Severe Neonatal Jaundice - Saba Bakht, Sohaib Riaz, Nidda Ayub, Syed Khurram Sajid (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of thrombocytopenia in neonates undergoing exchange transfusion of blood for severe neonatal jaundice. Methodology: Total 200 neonates fulfilling the selection criteria were included in the study from neonatology unit, The Madinah Teaching Hospital Faisalabad during Nov, 2020 to October 2022. An informed consent was taken from parents. Demographic information (name, age, gender, and contact) was obtained. Then all neonates underwent exchange transfusion under standard procedure. After exchange transfusion 3cc Blood sample was obtained with the help of a staff nurse by using butterfly needle and 5cc BD syringe under aseptic measures. Sample was sent to the laboratory of the hospital for platelet count. If platelet count was found below 100.000/dL, thrombocytopenia was labelled (platelet count in complete blood count is <100,000/dL assessed at the end of exchange transfusion). Results: In our study, the mean age of the patients was calculated as 15.17+4.85 days. Gender distribution reveals that 94(47%) were male and 106(53%) were females. Frequency of thrombocytopenia in neonates undergoing exchange transfusion of blood for severe neonatal jaundice was recorded in 15(7.5%) of the cases, and among them 7(46.7%) were between 1-14 days and 8(53.3%) were between 15-28 days of life, p-value=0.533, regarding gender 5(33.3%) were male and 10(66.7%) were females, p-value=0.203. Conclusion: We found that the rate of thrombocytopenia in neonates having blood exchange transfusion for severe neonatal jaundice was not significantly greater than the rate in other studies. However, our results are from a single site and need to be confirmed by additional multicenter local investigations. Keywords: Severe neonatal jaundice, exchange transfusion of blood, thrombocytopenia